Decision Making for Professions in Secondary Education Level Students: (Survey of SMA, MA, and SMK in Masamba) - Asriansyah Asriansyah (P3I Luwu Raya, 2020)
This research was conducted driven by concerns over the high number of unemployed, especially educated unemployment, and the high social problems that occur in students / students of secondary education age and level in the country. The assumption is, students who have a decision to pursue a particular profession in the future, will not do negative things that damage their ideals. This study questions the abilities and insights of high school, Madrasah Aliyah, and vocational high school students in making decisions about professions and jobs. The research was conducted in Masamba City from January to March 2019. The research sample was obtained opportunistically as many as 400 students. Data collection was carried out using interview and questionnaire techniques. The results showed that the majority of high school (SMA), Madrasah Aliyah (MA), and Vocational High School (SMK) students did not have a clear decision about the profession to be involved in.